Assessment of point-frame method to quantify wolf diet by scat analysis. - CIUCCI, Paolo; TOSONI, Elisabetta; BOITANI, Luigi (Wildlife Biology:Grenaavej 14 Kalo, Edit Office, DK 8410 Ronde Denmark:011 45 89 201509, EMAIL: hkl@dmu.dk, INTERNET: http://www.wildlifebiology.com, Fax: 011 45 89 201711, 2004)
Scat analysis is a widely used technique to assess food habits of wolves Canis lupus, but complete dissection and thorough hand separation of the undigested remains for their individual identification is laborious and time consuming. In addition, this technique is susceptible to inter-observer sources of error. Alternatively, the point-frame method allows systematic sampling of undigested remains of faecal samples and greatly reduces the processing time. Based on a sample of 200 wolf scats, we compared hand separation and point-frame methods using four widely used scat analysis quantification methods (frequency, volume and biomass models). Qualitative and quantitative estimates of the wolf diet showed close agreement between hand separation and point-frame procedures, but point-frame sampling allowed for an 85% reduction of the processing time. Given that the method is properly applied and its assumptions are met, we conclude that application of the point-frame method is reliable and more time effective than hand separation of wolf scat. The point-frame method could also provide a more rigorous sampling approach to reduce observer subjectivity as to what constitutes an accurate hand separation of undigested remains in scat.